Physical mapping of 45S and 5S rDNA and telomeric repeat loci in eight diploid hyacinth cultivars - He, Yuan-Hao; Su, Xiao-Qian; Xu, Zi-Han; Hu, Feng-Rong (Phytotaxa, 2022)
Hyacinth, one of the five best-selling bulbous flowers in the world, is a favored flower of garden landscapes in the spring. Hyacinth has a single origin, but there are many horticultural varieties. Physical mapping of ribosomal DNA (rDNA) and telomeric repeat loci by fluorescence in situ hybridization (FISH) is helpful to understand the genetic relationship and chromosome inheritance in hyacinth breeding. In this study, 45S rDNA, 5S rDNA and telomeric repeats were used as probes, the mitotic metaphase chromosomes of 8 diploid hyacinth cultivars were analyzed by FISH location, and their karyotype parameters were analyzed by Q-type cluster analysis. The results showed that two 45S rDNA loci were detected in all eight hyacinth cultivars, four 5S rDNA loci were detected in ‘Gypsy Queen’, and three were detected in other cultivars. In addition to the presence of telomere loci at both ends of chromosomes, seven telomere loci were detected in ‘Gypsy Princess’ and ‘Yellow Stone’, and eight telomere loci were detected in other cultivars. At the same time, when the euclidean distance between groups was 20, the eight hyacinth cultivars were clustered into three groups (‘Yellow Stone’, ‘Red Pearl’ and ‘Pink Pearl’), and ‘Gypsy Prince’ was a single group; the other four cultivars were in one group. The distribution of 45S rDNA loci in diploid hyacinth cultivars was relatively conservative, while the locus number and distribution of 5S rDNA and telomeric repeats were highly polymorphic. The FISH physical mapping in this study provides a basic understanding of the karyotype evolution of hyacinth species, which could increase the understanding of the evolutionary history and phylogenetic relationships of hyacinths.